Biskupi i prezbiterzy w Kościele w Rzymie w I i II wieku (część 2) - Misiarczyk, Leszek (Vox Patrum, 2025)
All sources relating to the Church of Rome confirm that it was led by πρεσβύτεροι in the sense of “elders”, or superiors of the community, sometimes identified with ἐπίσκοποι. However, never in sources related to Rome, was the term πρεσβύτεροι understood as the second degree of the ecclesiastical hierarchy, as in the Epistles of Ignatius of Antioch. The task of these bishops and elders was λειτουργία, i.e., leadership of the community, celebration of worship, as well as charity to needy brethren. However, nowhere in the sources does the phrase like “college of presbyters” appear. We have all been too seduced by the perspective of the Epistles of Ignatius of Antioch, in which a three-degrees hierarchy appears, and presbyters are the second degree of the Church hierarchy. On the other hand, depending on the evaluation of the list of bishops of Rome cited by Irenaeus, it cannot be ruled out that there was a monarchical episcopate in the Roman Church from the beginning, and the bishops continued to be referred to by the old generic term πρεσβύτεροι – “elders”, as the superiors of the community. The meeting of Polycarp, bishop of Smyrne and pope Anicetus confirms that in the middle of the II century there was a single bishop in Rome.